Evolution and Challenges of the Program of Payment for Environmental Services Implemented by the Empresade ServiciosPúblicosde Heredia S.A. - Solano, Vivian (2010)
The experience of the ESPH S. A. in the implementation of payments for environmental services (PES) is notable for being a scheme completely independent from the institutionalism of the Fondo Nacional de Financiamiento Forestal (Fonafifo). ESPH S. A. has a financial mechanism that comes from an item known as water rate, which represents the environmental cost to protect five watersheds located in the urban periphery of Heredia’s central region. The enterprise´s experience demonstrates that in sites with similar conditions, the PES is a tool that contributes to forest protection; however, it must be accompanied by other initiatives to offset the urban pressure exerted on the aquifer recharge areas.